Surgical Considerations in Dental Prosthetics: Implant-Supported Restorations vs. Traditional Bridges - Dr. Ali Mohammed Ali Aldossari; Dr.Sarra Mohsen Bejad Alotaibi; Dr. ‏Mousa Yahia Karyri; Dr. Abdullah Hassan Al Shari; Dr. Ali Ahmed Asiri; Dr. Rami Amin Gashgary; Dr.Mashael Obaid Alshahrani; DR. Raed Saleh Almanea; Turki Farhan Omish Alharbi; Dr. Mansour Ali Nasser Alhomaied (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Dental prosthetics has performed a crucial role in rehabilitation of patients with the lost teeth for years by providing the needed function, esthetics, and improved quality of life. Of all the available options to replace missing teeth, dental bridges and implant retained prostheses are perhaps the most well-known. Though both therapeutic models are efficient they have the major distinctions contemplating surgeries, further results, and terms for patients. It is, therefore, important to consider several clinical, aesthetic, and economic factors to arrive at a decision between these options, though only by dental practitioners and the patients. It will always be helpful and relevant to remember the surgical aspects of these prosthetic solutions while dental technology and materials improve over time. Aim of work: To examine the key surgical considerations in dental prosthetics, comparing implant-supported restorations and traditional bridges. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Surgical Considerations, Dental Prosthetics, Implant-Supported, Restorations and Traditional Bridges. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:The decision of whether to intervene surgically and provide implant supports or offer the more conventional bridgework depends on a number of factors, both surgical and functional as well as patients. On the one hand, the former has attractive features inherent to additive technologies while the latter has disadvantages typical for subtractive technologies, so the use of both technologies needs an individual approach in the dental prosthetics. An implant-supported restoration is the currently considered gold standard of patient care due to focuses on maintenance of treatment goals and integration with the body, while a traditional bridge is a more everyday structure offering reliable effectiveness at a lower cost. Since the technology in the field is on the right cultural bent, this combination of the aforementioned approaches is likely to increase and ensure that patients receive the best forms of prosthetic treatment for missing teeth. With this perspective and understanding of the challenges modern dentistry faces in prosthetics, dental practitioners and technicians have to go from identifying the problem and finding a solution in a creative yet sustainable manner to actually providing the patient with a new set of teeth that will increase that individual’s quality of life.